Compensatory quadrant-hyperhidrosis after contralateral intrathoracic surgery: a case report - Brodoehl Stefan; Witte Otto; Guenther Albrecht (Journal of Medical Case Reports, 2013)
Abstract Introduction Unilateral hyperhidrosis can be a neurological manifestation of irritations of the central or peripheral nervous system. Case presentation We present the case of a 67-year-old German man who had hyperhidrosis of his right upper body quadrant (including face, arm, and chest) following intrathoracic surgery of a left-sided pleural lipoma. Conclusion An isolated unilateral hyperhidrosis might occur after intrathoracic surgery. Besides anticholinergic drugs the use of botulinum toxin should be considered.